KONSEP PENDIDIKAN KARAKTER DALAM AL-QUR’AN - Haidar Hafiedz; Khusnul Wardan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This article aims to examine the concept of character education in the Qur’an as a fundamental foundation for shaping individuals with noble morals, integrity, and resilience in facing global challenges. This study employs a qualitative approach through library research, focusing on primary sources from Qur’anic verses and secondary sources such as books, academic articles, and relevant journals. The analysis applies content analysis to identify Islamic character values embedded in the Qur’an, including piety, honesty, trustworthiness, patience, gratitude, justice, benevolence, and humility. The findings reveal that Qur’anic-based character education emphasizes not only cognitive development but also a balanced cultivation of moral, spiritual, and social dimensions. These values are highly relevant to both formal and non-formal education as a means of strengthening the moral identity of younger generations. The study confirms that the Qur’an serves as a primary guideline for constructing a character education system that is adaptive to contemporary changes yet firmly rooted in divine principles. The implications highlight the necessity of synergy among educators, parents, society, and policymakers in creating a morally upright generation that is prepared to navigate the complexities of modern life.